#TITLE_ALTERNATIVE# - Darussalam, Mohammad
ABSTRACT: In consequence of certain undesired properties accompanying some of bone imaging agents such as 47Ca, 85mSr, and 18F, more attention has been paid to some Technetium-99m labeled phosphates such as 99mTc-pyrophosphate and 99mTc-polyphosphate and consequently more intensive studies have been performed. Similar to radionuclide Technetium-99m (99mTc), the biodistribution study of Technetium-99m labeled phosphates in nonpregnant and nonlactating animals and humans has been previously documented. However, studies on the biological behaviour of Technetium-99m labeled phosphate in experimental animal or human during pregnancy and lactation are limited. This study endeavours to obtain more basic information concerning the fate of taken up 99mTc labeled phosphates in different physiological conditions of the experimental animal such as pregnancy and lactation period. Some suggestions could consequently be made with respect to the possible application of those radioactive substances during the mentioned physiological conditions. Furthermore, the experiments elucidate comparatively the biodistribution of 99mTc-pyrophosphate and 99mTc-polyphosphate as well as 99mTc-pertechnetate in pregnant and lactating Wistar rats. The following aspects of the problem have been the focus of the investigation a. The maximum tissue radioactivity level and the length of time necessary to reach it in Wistar rat during various physiological conditions b. The comparative tissue radioactivity level of Technetium-99m labeled compound c. The placental passage of Technetium-99m labeled compounds as well as the relationship between the intrafetal radioactivity content and the fetal weight d. The transfer of Technetium-99m labeled compounds from mother animal to neonate via milk secretion e. The 99mTc-pyrophosphate uptake level in the fetal and neonatal tissues f. The radioactive substance recovery pattern in pregnant and lactating Wistar rats. The Technetium-99m labeled compounds are intravenously administered to pregnant Wistar rats on the last third period of gestation (on the 18th up to 19th day of gestation) and in the case of lactating Wistar rats the radio-active substances were applied shortly after the term. The activities of the administered radioactive solution are 300 uCi and 400uCi pro animal for the 99mTc-phosphates and 99mTc-pertechnetate respectively. The observation and measurement of the tissue radioactivity have been carried out at various time intervals 2, 4, 16, and 24 hour post injection. The observed tissues of Wistar rat are : blood, femur, muscle, liver, spleen, kidney, mammary glands, thyroid glands, placenta, amniotic fluid, reabsorbed embryo, fetus, and neonate including digestive tracts, urine, faeces, and some of the fetal and neonatal tissues. The experimental design used was the Completely Randomized Design (CRD) with 8 to 10 replication pro treatment The tissue radioactivities are expressed as the percentage (%) of the administered radioactivity per gram tissue (radioactivity concentration) as well as the percentage (%) of the administered radioactivity per organ (radioactivity retention): The conclusion drawn from the experimental results are There exist differences in the maximum tissue radioactivity level of the virgin, pregnant, and lactating Wistar rats as well as the differences in time period necessary to reach it shown by 99mTc-pyrophosphate and 99mTc-polyphosphatez In most cases, the tissue radioactivity levels of 99mTc-polyphosphate in both pregnant and lactating Wistar rats are significantly higher (a= 0,05) than that of 99mTc-pyrophosphate, except the liver and the spleen, which showed a converse pattern, The femur radioactivities of both 99mTc-pyrophosphate and 99mTc-polyphosphate in pregnant and lactating Wistar rats were shown to be significantly higher (a= 0,01) than that of 99mTc-pertechnetate, while the thyroid glands showed reverse radioactivity patterns. The other tissue radioactivity level of 99mTc-pertechnetate, except for the critical tissues lies approximately in between the two 99mTc-phosphate compounds, showed faster blood clearance in the last two intervals. The blood-removal value level of the 99mTc-labeled compounds in both pregnant and lactating Wistar rats increased in the following order : 99mTc-polyphosphate, 99mTc-pyrophosphate and 99mTc-pertechnetate. The labeled compounds 99mTc-pyrophosphate and 99mTc-polyphosphate as well as 99mTc-pertechnetate have demonstrated clearly the ability for placental passage. A positive linear correlation between the intrafetal radioactivity content and the fetal weight has been observed. The transfer of 99mTc-pyrophosphate and 99mTc-poly phosphate as well as 99mTc-pertechnetate from mother animal to neonate via milk secretion has also been observed. Both fetal and neonatal tissues showed incomplete uptake of 99mTc-pyrophosphate compared to the adults. Both 99mTc-pyrophosphate and 99mTc-polyphosphate were mainly recovered in the skeleton (bone tissue) of pregnant and lactating Wistar rats, Most of 99mTc-pertechnetate were recovered in the digestive tracts, liver, and urine of pregnant Wistar rats as well as in the digestive tracts and mammary glands of the lactating individuals.